2019
DOI: 10.21147/j.issn.1000-9604.2019.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of 18F-fluorodeoxyglucose positron emission tomography using Deauville criteria in diffuse large B cell lymphoma treated with autologous hematopoietic stem cell transplantation

Abstract: ObjectiveHigh-dose chemotherapy (HDC) followed by autologous hematopoietic stem cell transplantation (auto-HSCT) plays an important role in improving outcomes of diffuse large B cell lymphoma (DLBCL) patients. 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) has been widely accepted in response assessment and prediction of prognosis in DLBCL. Here, we report the value of 18F-FDG PET/CT pre- and post-HSCT in predicting outcomes of patients with DLBCL. MethodsDLBCL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…A few of studies have assessed the prognostic value of post-ASCT [ 18 F]F-FDG PET-CT for lymphoma [29][30][31][32][33][34]. Most of these studies have confirmed the prognostic value of post-ASCT [ 18 F]F-FDG PET-CT [29][30][31]. However, in Palmer's multivariate analysis, the post-ASCT [ 18 F]F-FDG PET-CT scan cannot predict the outcome for patients undergoing ASCT [32].…”
Section: Discussionmentioning
confidence: 99%
“…A few of studies have assessed the prognostic value of post-ASCT [ 18 F]F-FDG PET-CT for lymphoma [29][30][31][32][33][34]. Most of these studies have confirmed the prognostic value of post-ASCT [ 18 F]F-FDG PET-CT [29][30][31]. However, in Palmer's multivariate analysis, the post-ASCT [ 18 F]F-FDG PET-CT scan cannot predict the outcome for patients undergoing ASCT [32].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT cannot well predict the OS of patients, but there is a strong correlation between the detection results and PFS, indicating that 18 F-FDG PET/CT detection can effectively guide the subsequent clinical treatment options. Ying et al [34] presented that, based on multivariate analysis, HSC transplantation after HDC treatment could predict survival using 18 F-FDG PET/CT detection in patients with lymphoma. Based on the above content, 18 F-FDG PET/CT can not only effectively monitor various reactions (drug sensitivity, adverse reactions, etc.)…”
Section: Contrast Media and Molecular Imagingmentioning
confidence: 99%
“…Reference [34] PET results were associated with 3-year PFS [HR � 4.391, P � 0.001; HR � 7.607, P < 0.001] and OS (HR � 4.792, P � 0.008; HR � 26.138, P < 0.001).…”
Section: Research Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvage chemotherapy with individualized regimens such as ICE (ifosfamide, carboplatin and etoposide), GDP (gemcitabine, dexamethasone and cisplatin) or DHAP (dexamethasone, high-dose cytarabine and cisplatin) is recommended for relapsed/refractory patients. Autologous stem cell transplantation (ASCT) consolidation is recommended for transplant-eligible patients who achieved remission from salvage therapy ( 7 ). Clinical trials including chimeric antigen receptor T-cell immunotherapy (CAR-T) are options, especially for patients who are ineligible for ASCT or resistant to salvage therapy.…”
Section: Treatmentmentioning
confidence: 99%